A novel human colon signet-ring cell carcinoma organoid line: establishment, characterization and application. (19th November 2019) - Li, Yaqi; Wang, Renjie; Huang, Dan; Ma, Xiaoji; Mo, Shaobo; Guo, Qiang; Fu, Guoxiang; Li, Yuanchuang; Xu, Xiaoya; Hu, Xiang; Zhou, Yi; Deng, Yun; et al.
Abstract: Colon signet-ring cell carcinoma (SRCC) is a rare type of malignant dedifferentiated adenocarcinomas, and is associated with poor survival. However, an in-depth study of the biological features of SRCC is hindered by the lack of a reliable in vitro model of colon SRCC. Thus, the establishment of cell cultures from SRCC has become the most challenging task. Here, by harnessing the power of the organoid culture system, we describe the establishment of a human colon SRCC organoid line from a surgical sample from one patient with colon SRCC. The colon SRCC organoid line, YQ-173, was characterized for morphology, histology, ultrastructure and chromosome stability levels, showing that it resembles the histological and growth characteristics of the original tumor cells; xenografts were used to show that it also has a high tumor formation rate. RNA sequencing of YQ-173 compared with the normal tissue verified its mucinous nature. Capture-based targeted DNA sequencing combined with drug screening based on a bespoke 88 compound library identified that JAK2 might be a treatment target. An in vitro drug screening found that AT9283 and Pacritinib could be effective JAK2 inhibitors, which was consistent with the in vivo xenograft response. We report, for the first time, the establishment of an SRCC organoid line allowing in-depth study of SRCC biology, as well as a strategy to assess in vitro drug testing in a personalized fashion.